2010
DOI: 10.1051/epjconf/20100622014
|View full text |Cite
|
Sign up to set email alerts
|

The external and internal measurement impact on shear modulus distribution within cyclic small strains in triaxal studies into cohesive soil

Abstract: Abstract. The paper deals with comparison of tangent shear moduli G s of kaolin from Tułowice obtained from cyclic triaxial tests on the basis of external and internal reading in the small strains range (10 -5 ÷10 -3 ). The tests were carried out on a modernised test bed, enabling full saturation of specimens using the back pressure method as well as a precise internal measurement of strains by means of contactless microdisplacements sensors. The value of linearity factor L is one of adopted quality criteria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Whereas each series of CU tests was conducted at confining stresses equal to s' 3 = 20 kPa, 50 kPa, and 80 kPa (for RC and RC-G) and s' 3 = 100 kPa, 200 kPa, and 300 kPa (for K-G). The selection of confining pressure s' 3 = 100 kPa, 200 kPa, and 300 kPa for K-rubber waste mixture tests refers to earlier Jastrzębska's tests conducted on pure K [17,19,20,21]. In turn, the choice of confining pressure s' 3 = 20 kPa, 50 kPa, and 80 kPa for RC-rubber waste mixture tests sought to verify whether the expansive soil (weak soil) with the addition of rubber waste could be used for road or railway embankment construction, where the real transferred loads are usually less than 100 kPa.…”
Section: Triaxial Test Conditionsmentioning
confidence: 99%
“…Whereas each series of CU tests was conducted at confining stresses equal to s' 3 = 20 kPa, 50 kPa, and 80 kPa (for RC and RC-G) and s' 3 = 100 kPa, 200 kPa, and 300 kPa (for K-G). The selection of confining pressure s' 3 = 100 kPa, 200 kPa, and 300 kPa for K-rubber waste mixture tests refers to earlier Jastrzębska's tests conducted on pure K [17,19,20,21]. In turn, the choice of confining pressure s' 3 = 20 kPa, 50 kPa, and 80 kPa for RC-rubber waste mixture tests sought to verify whether the expansive soil (weak soil) with the addition of rubber waste could be used for road or railway embankment construction, where the real transferred loads are usually less than 100 kPa.…”
Section: Triaxial Test Conditionsmentioning
confidence: 99%
“…Soil in the range of small deformations is defined by the initial shear modulus G 0 (G max ) and constrained modulus E 0 (E max ). The above parameters are obtained on the basis of specialist field tests (Seismic Cone Penetration Test SCPT, Seismic Dilatometer Marchetti Test SDMT probes) and laboratory tests (triaxial compression apparatus [10], resonant column) [21].…”
Section: Importance Of the Subjectmentioning
confidence: 99%
“…measuring equipment and research methods (tests on soil compacting by means of Proctor apparatus, designation of the grain-size distribution in cohesive soils by means of aerometric analysis, designation of the cohesion and internal friction angle in triaxial apparatus, and direct shear apparatus, and compressibility module in oedometers, Terzaghie's principle for a two-phase medium by carrying out the saturation of soil samples by means of the gravitation method and the back pressure method, etc.). The results of such tests have been described in: [6,7,8,9,10,11,12,13,14]. A more detailed description of complicated research procedures may be found in Jastrzębska and Kowalska [15,16].…”
Section: Elaborations Describing Research In Geotechnical Laboratoriesmentioning
confidence: 99%